Potential of entomopathogenic fungi as biological control agents of diamondback moth (Lepidoptera: Plutellidae) and compatibility with chemical insecticides - Duarte, R. T. [UNESP]; Gonçalves, K. C. [UNESP]; Espinosa, D. J.L. [UNESP]; Moreira, L. F. [UNESP]; De Bortoli, S. A. [UNESP]; Humber, R. A.; Polanczyk, R. A. [UNESP] (Oxford University Press (OUP), 2016)
The objectives were to evaluate the efficiency of entomopathogenic fungi against Plutella xylostella (L.) and the compatibility of the most virulent isolates with some of the insecticides registered for use on cabbage crops. Pathogenicity tests used isolates of Beauveria bassiana, Metarhizium rileyi, Isaria fumosorosea, Isaria sinclairii, and Lecanicillium muscarium standardized at a concentration of 107 conidia/ml. Cabbage leaf discs were immersed in these suspensions, and after evaporation of the excess water, were placed 10 second-instar larvae of P. xylostella, totaling 10 leaf discs per treatment. Mortality was assessed 7 d after treatment, and the isolates that caused mortality >80% were used to estimate LC50 and LT50. The compatibilities of the most virulent isolates and the insecticides were tested from the mixture of these into the culture medium, and after solidifying, the medium was inoculated with an aliquot of the isolated suspension. The following parameters were evaluated: growth of the colony, number and viability of conidia after 7 d. The isolated IBCB01, IBCB18, IBCB66, and IBCB87 of B. bassiana, LCMAP101 of M. rileyi, and ARSEF7973 of I. sinclairii caused mortality between 80 and 100%, with LC50 and LT50 between 2.504 to 6.775 × 104 conidia/ml and 52.22 to 112.13 h, respectively. The active ingredients thiamethoxam and azadirachtin were compatible with the entomopathogenic fungi. The results suggest that the use of these isolates is an important alternative in the pesticidal management of P. xylostella, with the possible exception of the associated use of chemical controls using the active ingredients thiamethoxam or azadirachtin.
Keywords: biological control; chemical control; interaction; Plutella xylostella